The CbbQO-type rubisco activases encoded in carboxysome gene clusters can activate carboxysomal form IA rubiscos - Tsai, Candace Yi-Chin (2022)
The CO2-fixing enzyme rubisco is responsible for almost all carbon fixation. This process frequently requires rubisco activase (Rca) machinery, which couples ATP hydrolysis to the removal of inhibitory sugar phosphates, including the rubisco substrate ribulose 1,5-bisphosphate (RuBP). Rubisco is sometimes compartmentalized in carboxysomes, bacterial microcompartments that enable a carbon dioxide concentrating mechanism (CCM). Characterized carboxysomal rubiscos, however, are not prone to inhibition, and often no activase machinery is associated with these enzymes. Here, we characterize two carboxysomal rubiscos of the form IAC clade that are associated with CbbQO-type Rcas. These enzymes release RuBP at a much lower rate than the canonical carboxysomal rubisco from Synechococcus PCC6301. We found that CbbQO-type Rcas encoded in carboxysome gene clusters can remove RuBP and the tight-binding transition state analog carboxy-arabinitol 1,5-bisphosphate from cognate rubiscos. The Acidithiobacillus ferrooxidans genome encodes two form IA rubiscos associated with two sets of cbbQ and cbbO genes. We show that the two CbbQO activase systems display specificity for the rubisco enzyme encoded in the same gene cluster, and this property can be switched by substituting the C-terminal three residues of the large subunit. Our findings indicate that the kinetic and inhibitory properties of proteobacterial form IA rubiscos are diverse and predict that Rcas may be necessary for some α-carboxysomal CCMs. These findings will have implications for efforts aiming to introduce biophysical CCMs into plants and other hosts for improvement of carbon fixation of crops.